Analisis Manajemen Strategik Kepala Sekolah Dalam Meningkatkan Kompetensi Guru di SMP Purnama Ayah Kabupaten Kebumen - Muizah, Retno Ida (Media Manajemen Pendidikan, 2024)
The aim of this research is to produce: (1) analysis of the principal's strategic management in improving teacher competency at Purnama Ayah Middle School; (2) the role of school principals in improving teacher competency; (3) analysis of factors that support and hinder the strategic management of school principals in improving teacher competency.This type of research is descriptive qualitative. Data collection techniques were obtained from interviews, observation and documentation. This research was carried out at Purnama Ayah Middle School. The data analysis technique used is the Miles and Huberman model. Researchers collect data, reduce data, present data and draw conclusions along with verification. Checking the validity of the data is by increasing persistence and using source triangulation and technical triangulation.Based on the results of data analysis, conclusions can be drawn: (1) Purnama Ayah Middle School has implemented four management functions (planning, organizing, implementing, and monitoring and evaluating) well before the program was implemented and while the program was running; (2) Internal coordination has been running regularly and well; (3) analysis of supporting and inhibiting factors is carried out during program formulation using SWOT-based analysis.